OLEAGINOUS MICROORGANISMS AS SOURCE OF GAMMA LINOLENIC ACID - ANANIA ARJUNA; EKTA CHITKARA (International Journal of Pharma and Bio Sciences, 2015)
The valuable polyunsaturated gamma linolenic acid (fatty acid), having applications in foods and pharmaceuticals, can be produced at a high overall volumetric rate by cultivation of M.ramanniana. GLA obtained was identified by gas liquid chromatography and spectroscopic studies. No GLA was detected at zero time cultures broth. Bacterial and fungal cultures were screened for production of GLA.